2020
DOI: 10.2478/fhort-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Basil seeds as a source of antioxidants affected by fortification with selenium

Abstract: The work aimed to determine the potential of selenium incorporation into seeds of selected species of Ocimum spp. after fortification with a foliar solution of sodium selenate at a concentration of 50 g Se · ha−1. In a 2-year trial, the selenium content was determined by electrothermal atomic absorption method with Zeeman background correction. Modified spectrophotometric method (2,2-diphenyl-1-picrylhydrazyl [DPPH] assays) was used to rate the potential of oxidation– reduction components of basil seeds (AA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In particular, the antioxidant capacity (AOA) and total phenolic content (TPC) of basil seeds were determined by various research groups using the DPPH (2,2-diphenyl-1-picryl-hydrazyl-hydrate) and Folin-Ciocalteu methods, respectively, each reporting different values (Table 6). The results by Mezeyová et al [69] are not comparable with others, as the calculation formula was different. However, seeds from Pakistan presented lower values of TPC (4890 µg GA/g), and seeds from Iran demonstrated higher values (22,900-65,500 µg GA/g).…”
Section: Beneficial Properties Of Basil Seeds 61 Antioxidant Activitymentioning
confidence: 73%
See 2 more Smart Citations
“…In particular, the antioxidant capacity (AOA) and total phenolic content (TPC) of basil seeds were determined by various research groups using the DPPH (2,2-diphenyl-1-picryl-hydrazyl-hydrate) and Folin-Ciocalteu methods, respectively, each reporting different values (Table 6). The results by Mezeyová et al [69] are not comparable with others, as the calculation formula was different. However, seeds from Pakistan presented lower values of TPC (4890 µg GA/g), and seeds from Iran demonstrated higher values (22,900-65,500 µg GA/g).…”
Section: Beneficial Properties Of Basil Seeds 61 Antioxidant Activitymentioning
confidence: 73%
“…The results by Mezeyová et al [ 69 ] are not comparable with others, as the calculation formula was different. However, seeds from Pakistan presented lower values of TPC (4890 µg GA/g), and seeds from Iran demonstrated higher values (22,900–65,500 µg GA/g).…”
Section: Beneficial Properties Of Basil Seedsmentioning
confidence: 77%
See 1 more Smart Citation
“…The rising popularity of O.basilicum seeds and its gelatin-like consistency, has created an interest to use these seeds as an effective ingredient to enrich the steamed rice cakes. 6 It has also been reported that the polysaccharides proportion of basil seeds namely glucomannan, xylan, glucan and the presence of a highly branched arabinogalactan 7 contribute to the mucilaginous or gelatin like property. This property of the basil seed is utilized in the steamed rice cake preparation, instead of black gram, which is a prime ingredient and a causative factor for obtaining a soft textured steamed rice cake.…”
Section: Introductionmentioning
confidence: 99%
“…Humans have relied on medicinal plants and their products from prehistoric times all over the world. Basil (Ocimum basilicum L.) has already been demonstrated that it has antimycotoxigenic, antiradical, antioxidant, antifungal, and antibacterial properties (Mezeyová, 2020). Alkadi (2021) reported that Ocimum basilicum extract has antifungal properties against A. parasitiucus and A. flavus.…”
Section: Introductionmentioning
confidence: 99%